Service regularity investigation of fixed-route taxi during on-peak hours - Кузькін, Олексій Феліксович (Eastern-European Journal of Enterprise Technologies, 2015)
In conditions of high service frequency on city routes, which is characteristic of "on-peak" hours, often there are cases of group bus arrivals when buses, belonging to the same or different routes arrive at stops almost simultaneously. Taking into account such cases in assessing the service irregularity and average waiting time is the concern of the paper, because, from the passenger's point of view, each such case is seen as arrival of one bus. Functional dependences of the values of the relative service irregularity and the average waiting time on the value of the network service frequency on the stop, provided that the flow of buses arriving at the stop is the easiest were proposed and theoretically substantiated. A field examination of the service regularity of fixed-route taxi in the city of Zaporizhzhya (Ukraine) was performed, based on which, using the method of regression analysis, the dependences of the values of the relative service irregularity and average passenger waiting time on the mathematical expectation of service interval of buses on the route were obtained. According to the results of statistical processing of results of field surveys, it was found that in conditions of network service frequency of more than 30 units per hour, the flow of buses of different routes arriving at the stop is distributed according to the Poisson law. This allows to use the proposed theoretical approach to the calculation of the average passenger waiting time, which increases the accuracy of its determination for passengers who can travel several routes in the studied conditions.